Between the devil and the deep blue sea — Regional economic assistance under European portents - Conzelmann, Thomas (Raumforschung und Raumordnung | Spatial Research and Planning, 2005)
The joint task “Improvement of the Regional Economic Structure” has been fundamentally transformed since the beginning of the 1980’s against the background of its integration into the regional policy of the European Community. In addition to a successive narrowing of the range of political options, the emergence of a regional policy structure “parallel” to the joint task with the participation of the European level is notable. The reform of European Community regional policy in the context of the eastward enlargement of the European Union will still reinforce the repercussions on regional policy in the Federal Republic of Germany.